2014
DOI: 10.5120/ijais14-451265
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Classification of Abnormal Respiratory Sounds on a Resource-constraint Mobile Device

Abstract: Abnormal breath sounds like wheezes, crackles and stridor at times manifest similar morphologies and pathological features of lung airways obstruction. This may pose problems to proper diagnosis and evaluation of the underlying respiratory condition by human auscultation. In this study, the authors experimented with Time-Frequency threshold-dependent (TFTD) algorithm for detection and classification of breath sounds based on Smartphone. The TFTD algorithm computes important and distinct features of each breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Thus, Refs. [ 18 , 38 , 41 ] and our proposed system have lower computational complexities than Refs. [ 20 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Thus, Refs. [ 18 , 38 , 41 ] and our proposed system have lower computational complexities than Refs. [ 20 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the quartile frequencies in the power spectrum of asthma group were higher than that of healthy control group, and they considered that wheezing sounds contained the peak frequency which was above 150 Hz and was at least three times higher than the baseline level. Uwaoma et al developed a time frequency threshold-dependent (TFTD) algorithm to detect wheezing sounds in a smartphone [ 38 ]. The peak frequency, the number of consecutive harmonics, and the duration was used as the wheezing features, but they also indicated that the peak frequency of breathing sounds, that is highly similar to that of wheezing sounds, would easily result in the detecting failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, while these approaches enable precise wheezing detection, they are slow. Recent attempts to achieve higher sensitivity and efficient detection performance include the consideration of a set of criteria in the time-frequency domain [15][16][17][18][19][20][21][22][23]. These criteria pertain to the duration, pitch range, and magnitude of wheezes in the time-frequency representation of the wheezes obtained through spectrogram analysis.…”
mentioning
confidence: 99%